PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA ORGANISASI PT. SAMICK INDONESIA - Erfan Esnawan; Donny Dharmawan (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This study aims to determine the magnitude of the influence of leadership and competence on the organizational performance of PT. Samick Indonesia. This study uses Simple Random Sampling. The population in this study were employees of PT. Samick Indonesia. With 156 samples. Data collection techniques using questionnaires which then have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression. The results of this study indicate that, Leadership is able to improve Organizational Performance. Competence is able to improve organizational performance thus it can be concluded that leadership and competence have a positive and significant influence on the organizational performance of PT. Samick Indonesia.